Kajian indeks kualiti air di Lembangan Sungai Paka, Terengganu - Suhaimi Suratman; Mohamad Awang; Loh, Ai Ling; Norhayati Mohd Tahir (Universiti Kebangsaan Malaysia, 2009)
A study of the Water Quality Index (WQI) has been conducted at Paka River basin, Terengganu. It involved the measurements of dissolved oxygen, pH, biological oxygen demand, chemical oxygen demand, total suspended solids and ammonia at eight sampling stations. The results showed that all the sampling stations were in the clean status except for the two polluted stations situated at Rengat River and Rasau River. Nonetheless, the overall mean WQI value of Paka River basin was 72.4% and can be classified as class II with the status of slightly polluted. Results also showed that the effluents from oil-palm factories were the major contributor for deterioration of WQI values in the study area.